(untitled) (Journal of the College of Education for Women, 2019)
Image compression is an important tool to reduce the bandwidth and storagerequirements of practical image systems. To reduce the increasing demand of storagespace and transmission time compression techniques are the need of the day. Discretetime wavelet transforms based image codec using Set Partitioning In HierarchicalTrees (SPIHT) is implemented in this paper. Mean Square Error (MSE), Peak Signalto Noise Ratio (PSNR) and Maximum Difference (MD) are used to measure thepicture quality of reconstructed image. MSE and PSNR are the most common picturequality measures. Different kinds of test images are assessed in this work withdifferent compression ratios. The results show the high efficiency of SPIHT algorithmin image compression.